THE ROLE OF THE QUALITY OF BANKING GOVERNANCE ON THE DISCLOSURE OF THE MANAGEMENT COMMENTS REPORT IN ACCORDANCE WITH INTERNATIONAL AND LOCAL REQUIREMENTS - H. RASHEED, RAGHAD; E.YAGUOB, EBTEHAJ (International Journal of Psychosocial Rehabilitation, 2021)
The study aims to know the role in the application and commitment of some internationa indicators of institutional governance and mechanisms issued by the Central Bank of Iraq to enhance and increase disclosure in the report of management comments issued by economic units. To achieve the purpose of the study, a number of Iraqi banks listed in the Iraq Stock Exchange were selected (Al Ahli Bank of Iraq, Iraqi Trade Bank, Gulf Commercial Bank, Middle East Investment Bank, Mosul Bank for Development and Investment, Al-Mansour Bank for Investment, Baghdad’s Al-Ahli Bank, Sumer Commercial Bank, Trans Iraq Investment Bank) as a research sample. The study relied on the analytical descriptive approach and designed a checklist to collect data. The data was obtained from the annual reports of the banks and for the period from (2016) to (2019), which are available in the Iraqi Stock Exchange and the official websites of the banks of the study sample. It also relied on the Corporate Governance Guide issued by the Central Bank of Iraq for the year 2018, in addition to the (GMI) index issued by the American company (Governance Metrics International), in addition to its reliance on the Administrative Comments Index (Ma.Co.I) issued by the International Accounting Standards Board (IASB) year 2020. The study reached a number of conclusions, including the existence of a discrepancy in the commitment of the study sample banks to the mechanisms of quality governance. In addition to the discrepancy in the disclosure of the information included in the reports of the management comments by the banks of the research sample